2001
DOI: 10.1002/jmri.1088
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the factors responsible for burns during MRI

Abstract: Numerous reported burn injuries have been sustained during clinical MRI procedures. The aim of this study was to investigate the possible factors that may be responsible for such burns. Experiments were performed to investigate three possible mechanisms for causing heating in copper wire during MRI: direct electromagnetic induction in a conductive loop, induction in a resonant conducting loop, and electric field resonant coupling with a wire (the antenna effect). Maximum recorded temperature rises were 0.6°C f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 17 publications
(21 reference statements)
3
153
0
2
Order By: Relevance
“…Dempsey and Condon supposed that RF heating may take place in MR procedures by electromagnetic induction, formation of resonance circuit, and antenna effect. 23,24 In the present situations, in which the implant is present in the ‰ow of the eddy current, these mechanisms are thought to be related to RF heating.…”
Section: Rf-heating Mechanismmentioning
confidence: 95%
“…Dempsey and Condon supposed that RF heating may take place in MR procedures by electromagnetic induction, formation of resonance circuit, and antenna effect. 23,24 In the present situations, in which the implant is present in the ‰ow of the eddy current, these mechanisms are thought to be related to RF heating.…”
Section: Rf-heating Mechanismmentioning
confidence: 95%
“…A fundamental line of development for fMRI has been the pursuit of higher magnetic field strengths, which leads to super-linear gains in functional sensitivity (van der Zwaag et al, 2009), that can be traded for increased spatial resolution (Da Costa et al, 2011;Yacoub et al, 2008). Unfortunately, however, simultaneous EEG-fMRI acquisitions at ultra-high field suffer from various undesirable interactions that can degrade data quality and potentially compromise subject safety (Dempsey et al, 2001;Neuner et al, 2014). Safety concerns have been effectively moderated (Lemieux et al, 1997;Noth et al, 2012), and although EEG components can reduce the signal-to-noise ratio (SNR) of MR images, numerous studies have found that losses in temporal SNR remain acceptable for fMRI, even at ultra-high field strengths with fairly high electrode densities (Jorge et al, 2015;Luo and Glover, 2012;Mullinger et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…4 According to the IEC recommendation, the upper limit in the Japanese Industrial Standards (JIS) was also reviewed in 1999 5 and provided for an upper limit of 2.0 W/kg for 6 min average as the usual operation mode and 4.0 W/kg for 15 min average as theˆrst-level operation mode, which is the same as the IEC standard. However, risk of burn accidents remains during MR imaging following these standards, [6][7][8][9] most resulting from contact between the skin of the human body and the cable of the electrocardiography monitor, oxygen color saturation monitor, or RF receiving coil. 10 Knopp's group has also reported cases where burning occurred during MR imaging procedures without such environmental conditions.…”
Section: Introductionmentioning
confidence: 99%